Encapsulation of Clove Oil within Ca-Alginate-Gelatine Complex: Effect of Process Variables on Encapsulation Efficiency - Agung Ari Wibowo; Ade Sonya Suryandari; Eko Naryono; Vania Mitha Pratiwi; Muhammad Suharto; Naila Adiba (Politeknik Negeri Malang, 2021)
Owing to the properties such as analgesic, clove oil is commonly used as medicine, antibacterial, antioxidant, and antimicrobial drugs. The possibility of clove oil encapsulation as a solid macrocapsule was studied by making Ca-Alginate-Gelatine macrocapsules. The process variables used were variations in Alginate concentration of 1% and 1.5% w/v, and the mass ratio between alginate-gelatine was varied between 1: 4, 1: 6, and 1: 8 w/w. In addition, variations in the concentration of CaCl2 (10%, 20% and 30% w/v) as a cross-linking agent for the formation of Ca-Alginate complexes were also used as process variables. The increase of alginate, gelatine and CaCl2 concentration seems to decreased the encapsulation efficiency because of the limitation of the free space volume formed in the Ca-Alginate-Gelatine matrix. The highest encapsulation efficiency (93.08%) was obtained in the use of Alginate 1% w/v, with a ratio of alginate to gelatine 1: 4 and cross-linking in a 10% w/v CaCl2 solution for 15 minutes.